Acoustics : sound fields and transducers - Beranek, Leo L. (Leo Leroy), 1914-2016 (Academic Press, 2012)
Acoustics: Sound Fields and Transducers is a thoroughly updated version of Leo Beranek's classic 1954 book that retains and expands on the original detailed acoustical fundamentals while adding practical formulas and simulation methods. Serving both as a text for students in engineering departments and as a reference for practicing engineers, this book focuses on electroacoustics, analyzing the behavior of transducers with the aid of electro-mechano-acoustical circuits. Assuming knowledge of electrical circuit theory, it starts by guiding readers through the basics of sound fields, the laws governing sound generation, radiation, and propagation, and general terminology. Numerical examples and summary charts are given throughout the text to make the material easily applicable to practical design. It is a valuable resource for experimenters, acoustical consultants, and to those who anticipate being engineering designers of audio equipment.